2018
DOI: 10.1080/02699206.2018.1445291
|View full text |Cite
|
Sign up to set email alerts
|

Time reference in nonfluent and fluent aphasia: a cross-linguistic test of the PAst DIscourse LInking Hypothesis

Abstract: Recent studies by Bastiaanse and colleagues found that time reference is selectively impaired in people with nonfluent agrammatic aphasia, with reference to the past being more difficult to process than reference to the present or to the future. To account for this dissociation, they formulated the PAst DIscourse LInking Hypothesis (PADILIH), which posits that past reference is more demanding than present/future reference because it involves discourse linking. There is some evidence that this hypothesis can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
(77 reference statements)
0
17
1
Order By: Relevance
“…[washed your hair]). No dissociation was found between performance for past and future tense (see also Fyndanis et al, 2018).…”
Section: Discourse Linking Time Reference and The Padilihmentioning
confidence: 88%
See 1 more Smart Citation
“…[washed your hair]). No dissociation was found between performance for past and future tense (see also Fyndanis et al, 2018).…”
Section: Discourse Linking Time Reference and The Padilihmentioning
confidence: 88%
“…Bastiaanse et al (2011) found that past time reference was selectively impaired in both production and comprehension for both Turkish and English speakers with aphasia (see also Jonkers and De Bruin (2009) for Dutch; Yarbay Duman and Bastiaanse (2009) for Turkish). However, several studies have reported no significant differences between impairment in reference to the past, present, and future (Fyndanis et al, 2018(Fyndanis et al, , 2012Wenzlaff & Clahsen, 2004). Fyndanis et al (2012), investigated the ability of two Greek-speaking agrammatic individuals to produce tense and aspect by means of transformational sentence completion tasks: the participants were asked to make a transition from one (sample) time reference (i.e., Tomorrow you will wash your hair) to another time reference on the basis of a temporal adverbial cue (i.e., Yesterday you .…”
Section: Discourse Linking Time Reference and The Padilihmentioning
confidence: 98%
“…This is so because, to perform this task, participants had to both encode an abstract, prephonological feature (+PERFECTIVE or −PERFECTIVE) other than that encoded in the verb form of the SS, and to retrieve a corresponding verb form/inflection. Hence, our design does not allow us to detect the exact nature of the deficit in grammatical aspect that emerged in Greek MS. (For suggestions on how to tease apart encoding from retrieval processes, see Fyndanis et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…investigated the ability of two Greekspeaking agrammatic individuals to produce tense and aspect by means of transformational sentence completion tasks: the participants were asked to make a transition from one (sample) time reference (i.e., Tomorrow you will wash your hair) to another time reference on the basis of a temporal adverbial cue (i.e., Yesterday you ... [washed your hair]). No dissociation was found between performance for past and future tense (see alsoFyndanis et al, 2018).Other studies have also demonstrated incompatibility with the PADILIH concerning the future. Martínez-Ferreiro and Bastiaanse (2013) examined Catalan and Spanish in both production and comprehension.…”
mentioning
confidence: 63%